2016
DOI: 10.14382/epitoanyag-jsbcm.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical activation of power station fl y ash by grinding – A review

Abstract: Power station fly ash has good application possibilities mainly in the construction industry, nevertheless, significant amount is landfilled due to their relatively low reactivity and heterogeneity. Hydraulic properties of fly ashes can be tailored by mechanical activation achieving a higher added value product, for example supplementary cementing materials (scms). the improved properties are higher specific surface area and desired particle size distribution (containing submicron size particles) as well as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The mechanical activation has been applied to increase the chemical reactivity of several minerals [10] with good commercial success, especially for leaching complex sulfides [11]. In a recent paper, Mucsi [12] reports the mechanical activation of fly ash and cement [9] in order to improve their performance as hydraulic binders. On the other hand, Sekulica [13] found that cement treated mechanically reported a compression stress 58% higher than an inactivated sample of similar composition; also reported that endothermic and exothermic reactions proceed at lower temperatures as indication of increased reactivity of mechanically activated sample.…”
Section: Limestone Calcination With Heva Systemmentioning
confidence: 99%
“…The mechanical activation has been applied to increase the chemical reactivity of several minerals [10] with good commercial success, especially for leaching complex sulfides [11]. In a recent paper, Mucsi [12] reports the mechanical activation of fly ash and cement [9] in order to improve their performance as hydraulic binders. On the other hand, Sekulica [13] found that cement treated mechanically reported a compression stress 58% higher than an inactivated sample of similar composition; also reported that endothermic and exothermic reactions proceed at lower temperatures as indication of increased reactivity of mechanically activated sample.…”
Section: Limestone Calcination With Heva Systemmentioning
confidence: 99%
“…High speed milling/grinding with pin mills or disintegrator is a type of high energy milling, which involves supply of energy in large amounts in a short duration of time with high power pulses [1]. In this way the amount of energy which is supplied to a solid material is much more than in conventional mills, with almost the same input power supplied [2].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the low hydraulic activity of serpentine, we employed a pre-treatment step of mechanical activation. The efficiency of mechanical activation for increasing the reactivity of solids is well established [25][26][27][28], and is a particularly effective technique for improving the mechanical properties of alkali-activated materials [29][30][31][32][33][34][35]. The term "mechanical activation" (MA) in this paper refers to the structural-chemical changes on the surface and in the bulk of minerals caused by milling.…”
Section: Introductionmentioning
confidence: 99%